Organizing the classes consideri Organizing the classes considering the students’ learning styles - Majidova, Gulruh (Maktabgacha taʼlim jurnali, 2022)
Abstract: The article highlights the information about the learning styles that the students employ in their learning process and their types. As individuals are different from each other in their character they have different learning styles one of which dominates the other. Identifying their learning style and using it will help them to acquire the subject without much effort. In the article some techniques are suggested for the teachers and students within 4 learning styles and they will be helpful to organize their teaching and learning routines.